Online pain neuroscience education and graded exposure to movement in breast cancer survivors: protocol of a randomized controlled trial - Martínez-Miranda, Patricia; Casuso-Holgado, María Jesús; García-Muñoz, Cristina; Muñoz-Fernández, María Jesús; Jiménez-Rejano, José Jesús (Frontiers in Medicine, 2024)
Introduction Cancer-related chronic pain is an important sequelae that damages the quality of life of breast cancer survivors. Pain neuroscience education and graded exposure to movement are therapeutic tools that have been shown to be effective in the management of chronic pain in other populations. However, there are no previous studies that combine them after breast cancer. Objective To evaluate the effectiveness of an online physiotherapy focused-person program which combines pain neuroscience education and graded exposure to movement for quality of life improvement in breast cancer survivors. Methodology This protocol is a randomized controlled trial with a sample size of 40 breast cancer survivors with pain in the last 6 months. Participants will be allocated to the experimental or control group using a fixed size block randomization method. The evaluator and statistician will be blinded to participant allocation. Participants in the experimental group will receive a 12-week intervention based on pain neuroscience education and therapeutic yoga as a graded exposure to movement exercise; participants in the control group will continue with their usual cancer-related symptoms care. Both groups will receive an education booklet. The main outcome will be quality of life, measured by the Functional Assessment of Cancer Therapy – Breast (FACT–B+4); secondary, four outcomes related to pain experience (catastrophising, self-efficacy, kinesiophobia and fear-avoidance behaviors) will be also assessed. All variables will be assessed by two blinded evaluators at four timepoints. A mixed-model analyses of variance ANOVA (2 × 4) will be used to study the effects of the treatment on the dependent variables. All statistical tests will be performed considering a confidence interval of 95%. SPSS program will be used for the data analysis. Discussion This research is expected to contribute to breast cancer rehabilitation field. The proposed intervention is also expected to improve self-care skills related to chronic pain and to empower women regarding the management of their symptoms and quality of life. Clinical trial registration:https://clinicaltrials.gov/, NCT04965909.